THE SEMATIC ANALYSIS OF SOME LENGOLA SONGS - Justin LUMALIZA MALISAWA (IJRDO - Journal of Social Science and Humanities Research, 2024)
In this article, we wanted to show our readers that Africa where the black man is located has a culture and the latter has a positive impact on the formation of the human being in the environment where he lives. Here we have chosen the Lengola people, a community located in the Ubundu Territory, Tshopo Province in the Democratic Republic of Congo. This population has a very rich cultural diversity and given the needs that motivated the development of this article we have taken only one aspect: “Lengola songs” because not only do they entertain but they also educate. When the white man arrived with colonization, certain African cultural values ​​were abandoned by blacks for the benefit of Western civilization. And this domination of white culture over that of blacks tends to cause the latter to disappear to the detriment of the new generation. If nothing is done to preserve it, the new generation risks missing this cultural heritage. Hence the motivation for said article.